La decisión de la Corte Internacional de Justicia sobre excepciones preliminares en el caso de Nicaragua vs. Colombia (2010)
This article is divided into three main parts. The fi rst part presents the precedents in the case relating to delimiting the Caribbean Sea boundary between Nicaragua and Colombia. It analyzes the competence of the International Court of Justice – ICJ (the Court) in accordance with Article 36 of the Statute of the Court; consequently, it studies the Declaration of the acceptance of the Competence of the Court presented by Colombia to the Permanent Court of International Justice in 1937 as well as the Bogota Pact of 1948 as to its applicability and breadth as regards the 1928 EsguerraBárcenas Treaty. The second part presents a detailed analysis of the decision of the Court on the preliminary exceptions in which it was determined that the sovereignty of the islands of San Andres, Providencia, and Santa Catalina was Colombian, that the Esguerra-Bárcenas Treaty was not treaty delimiting maritime boundaries and that it (the Court) was competent to get to the foundation of the matter. The third part sets out the actions which still must be completed relative to the foundation of the case.